Supervisory arbitrage and real effects - Beck, Thorsten; Silva-Buston, Consuelo; Wagner, Wolf (Journal of Corporate Finance, 2025)
We examine the effects of cross-border supervisory arbitrage on corporate lending and firm performance. We show that subsidiaries of banking groups improve loan conditions for firms when the group’s opportunities to take risks in other countries are curbed. The expansion in lending is targeted towards firms of higher quality and firms that the group is already familiar with. The improved lending conditions have positive real effects, allowing recipient firms to increase capital spending and leading to higher profits. Taken together, our results suggest that there can be benefits for firms in countries that receive lending inflows due to the supervisory arbitrage.